World Economy Winter 2023: Strong headwinds for global economic activity - Klaus-Jürgen Gern; Stefan Kooths; Nils Sonnenberg; Jan Reents; Ulrich Stolzenburg (Kiel Institute for the World Economy (IfW Kiel), 2023)
The global economy held up better than expected in the face of the inflation shock and the massive tightening of monetary policy in 2023, even if the economic expansion was moderate. Inflation is now falling swiftly and monetary policy is expected to start cutting interest rates in the first half of 2024. However, there are currently scant signs that global outlook will meaningfully improve in the near term. In the advanced economies, a high level of policy uncertainty is weighing on growth while fiscal policy stimuli are waning. In China, economic momentum remains subdued due to structural problems. Overall, we expect global production - measured on a purchasing power parity basis - to increase by 2.9 percent in the coming year, following 3.1 percent in 2023. For 2025, we expect global growth to pick up to 3.2 percent. We have thus revised upwards our forecast for 2023 and 2024 slightly - by 0.1 percentage points - compared to our September report. Although unemployment in the advanced economies will increase slightly going forward, it will remain historically low. Inflation will continue to fall and generally approach target levels again by 2025.
Keywords: 330